Charge Exchange Ion Losses in Saturn's Magnetosphere. Issue 10 (5th October 2021) - Sontag, A.; Clark, G.; Kollmann, P.
Abstract: While various source and loss processes have been proposed for ions in Saturn's magnetosphere, it is not yet well understood what role they play in different regions. In this study, we use a physical model of charge exchange to predict how proton and water group ion intensity profiles evolve over time and compare the results to MIMI/CHEMS measurements collected during the Cassini mission. First, we divide the CHEMS data into inbound and outbound half‐orbit segments, and create intensity profiles for 3–220 keV H + and W + ions between 5 and 15 Saturn radii, then using the inbound half‐orbits as initial conditions, we find qualitative similarities between measured and predicted outbound intensity profiles. This result is important because it provides strong evidence that charge exchange is the dominant loss process for these species in this region. The observed rate of charge exchange also presents information on the density of Saturn's neutral torus. We suggest that data‐model discrepancies in the water group ions may be an indication of a significant presence of ions with the water group mass that are multiply charged. Key Points: Survey of suprathermal proton and water group ions in Saturn's magnetosphere show strong variability at <1 MeV Data comparisons to a physical model suggest that charge exchange plays a key role in removing suprathermal ions between 5 and 15 RS This result is important for better understanding ion‐neutral interactions and loss processes in Saturn's magnetosphere